Towards configuring the neolithisation of Aegian Turkey - Çilingiroglu, Çiler (Documenta Praehistorica, 2013)
Increasing field work in the Izmir region has produced much sought tangible evidence about the ways in which food-producing communities emerged in the Aegean. Focusing on the archaeological and zooarchaeological data from Ulucak and neighboring sites, the authors discuss the possible mechanisms of initial farmer-herder dispersals into the region. The authors stress that the lack of pre-Neolithic strata in the eastern Aegean impedes a full understanding of forager-farmer interactions in the early Holocene.
Keywords: Izmir; neolitik; poljedelstvo; Turčija; Turkey